Self-healing juvenile cutaneous mucinosis in a 3 years old child. - Fratoni, S.; Fabbri, F.; Niscola, P.; Borrelli, L.; Alaggio, R. (European Journal of Pediatric Dermatology, 2020)
Self-healing juvenile cutaneous mucinosis (SHJCM) is a rare idiopathic disease clinically characterized by papules and subcutaneous nodules that suddenly arise in full well-being children and spontaneously regress in 2-12 months. Here was reported a typical case in a 3-year-old boy who self-healed in 9 months and did not undergo relapses or complications in the following 10 years. Differential diagnosis of SHJCM from other conditions such as cutaneous mucinosis of infancy and proliferative fasciitis was also discussed.